PREDICTING OF THE GOODS LIFECYCLES - L. B. Shabanova; V. N. Kushnirenko (Russian Journal of Economics and Law)
Under the conditions of the accelerated scientific-technological progress and social development the goods, possessing value, may loose their consumer value and, consequently, are extruded from the market by other goods with higher consumer value. In connection with that the significance of predicting of the goods lifecycles on the basis of studying their graphic models increases.